A Critical Review on Nano-Silica Reinforced Polyester-Based Glass Fiber Reinforced Polymer Composites: Ulasan Kritis tentang Komposit Polimer Berbahan Dasar Serat Kaca yang Ditingkatkan dengan Nano-Silika dan Polyster - Fatima Ghazi Edem (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Glass fiber reinforced polymer composites based on polyester matrices are widely applied in engineering due to favorable strength-to-weight ratio, corrosion resistance, and economic viability. Specific Background: Despite these advantages, their tensile and flexural performance is often limited by weak fiber–matrix interfacial bonding and matrix brittleness. Recent studies have reported that nano-silica incorporation may modify matrix behavior and improve stress transfer mechanisms. Knowledge Gap: However, a structured conceptual integration linking nano-silica content, dispersion quality, and interfacial bonding efficiency in polyester-based GFRP systems remains insufficiently synthesized in the literature. Aims: This critical review proposes an analytical framework to explain the interrelationship between nano-silica loading, particle dispersion, and mechanical response in polyester GFRP composites. Results: Literature findings consistently indicate that low to moderate nano-silica contents (0.5–1.0 wt%) with uniform dispersion contribute to improved tensile and flexural behavior, reduced micro-void formation, and enhanced load transfer, whereas excessive loading leads to particle agglomeration, stress concentration, and mechanical degradation. Novelty: The study integrates dispersed experimental evidence into a unified conceptual model without introducing new experimental data. Implications: The proposed framework offers theoretical guidance for optimizing nano-silica modified GFRP systems while maintaining cost feasibility and conventional fabrication compatibility. Keywords: Nano-Silica, Polyester GFRP, Filler Dispersion, Interfacial Bonding, Mechanical Properties Key Findings Highlights 1. Optimal nanoparticle loading occurs within a narrow low-percentage range. 2. Particle clustering correlates with premature cracking mechanisms. 3. Microstructural uniformity governs stress transfer efficiency.